Tuning of phase content, microstructure and thermal expansion of MgPSZ. Issue 3 (1st February 2023) - Starykevich, M.; Rondão, A.I.B.; Grilo, J.P.F.; Marques, F.M.B.
Abstract: MgO partially stabilized zirconia (xMgPSZ, with x = 3–14 mol% MgO) was prepared by a ceramic route, starting from pure metal oxides. 7.5MgPSZ, the focus of this work, was sintered at 1700 °C and cooled at various rates (1, 2 or 4 °C/min), without or with 1 or 2 intermediate dwells (1400, 1300, and 1000 °C), and dwell durations (1–6 h). Customized thermal expansion (TE) data analysis is used to estimate the monoclinic (M) phase content (with discrimination between large and small particles), while powder X-ray diffraction (XRD) provides an accurate cubic (C) phase assessment. With the tetragonal (T) phase content determined from balance to 100%, detailed sets of structural (M, C, T) and microstructural information (M particle size), are grouped in novel radar-type charts. Original benchmarking exercises using literature data on up thermal shock resistance and the characteristics of a commercial MgPSZ, provide unique insights on the thermal performance of these materials, and property tuning rationale. Graphical abstract: Cooling profiles determine the (C-T-M) phase characteristics, global thermal expansion (TE*), and up thermal shock performance. Image 1 Highlights: Structural, microstructural, and thermal characterization of MgPSZ with distinct characteristics. Customized analysis of thermal expansion data to examine phase composition and particle size effects. Radar charts highlight the effects of cooling profiles on phase characteristics and thermal behavior. Benchmarking of materials using literature data and commercial MgPSZ characteristics.